2009
DOI: 10.1051/0004-6361/200913062
|View full text |Cite
|
Sign up to set email alerts
|

GRB 090426: the farthest short gamma-ray burst?

Abstract: Aims. With an observed and rest-frame duration of <2 s and <0.5 s, respectively, GRB 090426 could be classified as a short GRB. The prompt detection, both from space and ground-based telescopes, of a bright optical counterpart to this GRB offered a unique opportunity to complete a detailed study. Methods. Based on an extensive ground-based observational campaign, we obtained the spectrum of the optical afterglow of GRB 090426, measuring its redshift and obtaining information about the medium in which the event… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 25 publications
(25 reference statements)
3
93
0
1
Order By: Relevance
“…See however Levan et al (2007). One possible exception is the case of GRB 090426 at z = 2.609 (Levesque et al 2010;Antonelli et al 2009;Zhang et al 2009) for which absorption line spectroscopy of the afterglow was successfully obtained, but may be considered on balance by the authors to be associated with the population of long gamma-ray bursts. The host galaxies of the short bursts were found initially to be mostly elliptical galaxies, e.g., GRB 050509B (Gehrels et al 2005;Bloom et al 2006) and GRB 050724 (Berger et al 2005;Gorosabel et al 2006) and that an old progenitor population was required.…”
Section: Discussionmentioning
confidence: 99%
“…See however Levan et al (2007). One possible exception is the case of GRB 090426 at z = 2.609 (Levesque et al 2010;Antonelli et al 2009;Zhang et al 2009) for which absorption line spectroscopy of the afterglow was successfully obtained, but may be considered on balance by the authors to be associated with the population of long gamma-ray bursts. The host galaxies of the short bursts were found initially to be mostly elliptical galaxies, e.g., GRB 050509B (Gehrels et al 2005;Bloom et al 2006) and GRB 050724 (Berger et al 2005;Gorosabel et al 2006) and that an old progenitor population was required.…”
Section: Discussionmentioning
confidence: 99%
“…These values make GRB 090205 consistent with the observed E p,i −E γ,iso correlation (Amati et al 2008), which is known to be followed only by long GRBs (see also Piranomonte et al 2008) and proposed as an indicator of GRBs with a massive stellar collapse origin (type II GRBs, Zhang et al 2009). The E p,i −E γ,iso correlation has indeed been used to support the long classification of a few rest-frame short duration bursts such as GRB 090423 (Salvaterra et al 2009) and GRB 090426 (Antonelli et al 2009). A type II classification for GRB 090205 is also supported by applying the classification method reported in Lv et al (2010), which implies that = E γ,iso,52 /E p,z,2 5/3 ∼ 0.26, where E γ,iso,52 = E γ,iso /10 52 erg and E p,z,2 = E p (1 + z)/10 2 keV.…”
Section: Burst Classificationmentioning
confidence: 98%
“…The existence of the Amati relation, discovered when analyzing the BeppoSAX long duration bursts, has been confirmed by studying a sample of GRBs observed by Swift, intense or soft, with available measurements of redshift and spectral parameters, and also by HETE-2 and Konus/WIND. When the "afterglow revolution" allowed the redshift estimation of also some short GRBs, it was found that these bursts are inconsistent with the Amati relation, holding instead for long GRBs (Amati 2006(Amati , 2010Antonelli et al 2009). The most recent updating of the correlation (95 GRBs with the data available up to April 2009) also includes two high-energetic events detected by Fermi (GRB 090323 and GRB 080916C), which are fully consistent with the E p,i -E iso relation (Amati et al 2009).…”
Section: Grb 071227 Within the Amati Relationmentioning
confidence: 99%